Время набоковского Дара – забавы хронического мистификатора - Levina-Parker, Maša; Levin, Michail (Wiener Slawistischer Almanach, 2022)
The purpose of this article is two-fold: to establish the year in which the novel begins, and, secondly, to show what literary devices are used to confuse the reader. The prevailing view is that the year is 1926, based on Nabokov’s own words. The text of the novel, however, points to either 1925 or 1927. A further investigation shows one of these dates to be true (1925) and the other false. 1926 is clearly impossible to reconcile with the text. The temporal dimension of the novel is constructed as a mystery, akin to that of a detective story, and needs deciphering. This invites comparisons with Belyi’s Peterburg and Platonov’s Chevengur. There are important similarities and dissimilarities between the three novels. The analysis in part supports Genette’s typology of manipulations with narrative time, but it also suggests how Genette’s model can be adapted. The article argues that this analytical model works best for Chevengur, less for Dar, and least of all for Peterburg. The generalizations made by Genette on the basis of his analysis of Proust’s chronicle appear to reflect some very important, but specific rather than universal, devices for time-games.